GlnR Activation Induces Peroxide Resistance in Mycobacterial Biofilms - Yang, Yong; Richards, Jacob P.; Gundrum, Jennifer; Ojha, Anil K. (Frontiers in Microbiology, 2018)
Mycobacteria spontaneously form surface-associated multicellular communities, called biofilms, which display resistance to a wide range of exogenous stresses. However, a causal relationship between biofilm formation and emergence of stress resistance is not known. Here, we report that activation of a nitrogen starvation response regulator, GlnR, during the development of Mycobacterium smegmatis biofilms leads to peroxide resistance. The resistance arises from induction of a GlnR-dependent peroxide resistance (gpr) gene cluster comprising of 8 ORFs (MSMEG_0565 -0572). Expression of gpr increases NADPH to NADP ratio, suggesting that a reduced cytosolic environment of nitrogen-starved cells in biofilms contribute to peroxide resistance. Increased NADPH levels from gpr activity likely supports the activity of enzymes involved in nitrogen assimilation, as suggested by a higher threshold of nitrogen supplement required by a gpr mutant to form biofilms. Together, our study uniquely interlinks a nutrient sensing mechanism with emergence of stress resistance during mycobacterial biofilm development. The gpr gene cluster is conserved in several mycobacteria causing nosocomial infections, offering a possible explanation for their resistance to peroxide based sterilization of medical equipment.